Physiology and pharmacology of glucagon-like peptide-1 receptor - D. V. Kurkin; D. A. Bakulin; E. I. Morkovin; V. I. Petrov; A. V. Strygin; K. N. Koryanova; Yu. V. Gorbunova; Yu. A. Kolosov; O. V. Ivanova; E. V. Pavlova; M. A. Dzhavakhyan; A. V. Zaborovsky; et al. (Фармация и фармакология (Пятигорск), 2024)
Modern approaches to the treatment of type 2 diabetes mellitus (T2DM) are aimed not only at glycemic control, but also at reducing cardiovascular risks. The increasing prevalence of the disease and the need for effective treatment options highlight the importance of glucagon-like peptide-1 (GLP-1) receptor agonists in the pharmacotherapy structure.The aim of the work was to review the literature regarding the physiology of GLP-1 and the therapeutic potential and development trends of its agonists.Materials and methods. The search for the review materials was carried out using the abstract databases of PubMed, Google Scholar and e-Library. The search was carried out for publications from 2000 to 2023, using the following keywords: “GLP-1”; “GLP-1R agonists”; “GIP”; “exenatide”; “liraglutide”; “dulaglutide”; “semaglutide”; “lixisenatide”; “albiglutide”; “taspoglutide” taking into account various spellings.Results. The interaction of almost all food components with enteroendocrine cells of the intestine leads to the secretion of incretins (primarily GLP-1) into the blood, triggering a complex of physiological reactions aimed primarily at the rapid utilization of incoming glucose (regulation of insulin and glucagon secretion), as well as the central regulation of dietary behavior (slowing gastric emptying and the formation of a feeling of satiety). A wide distribution of the GLP-1 receptor in various tissues and organs, its connection with intracellular signaling cascades aimed at launching energy-consuming remodeling (recovery) processes in endothelial cells, heart, neurons, beta cells, etc., is the basis for a wide range of pleiotropic effects of GLP-1 unrelated to its hypoglycemic effect. The discovery of synthetic GLP-1 receptor agonists with a long period of action has made it possible not only to therapeutically influence various parts of carbohydrate metabolism disorders, but also to increase the functional reserves of the target diabetes organs, reducing the risk of developing complications of the disease. Incretin-like drugs are well tolerated, with nausea being the most common side effect. The factors limiting a wider use of the drugs include their high cost and the preferred form of a subcutaneous solution. The current research is focused on the development of long-acting, oral, dual and triple agonists, fixed-dose combinations, and small molecule drugs.Conclusion. GLP-1 receptor agonists are a class of effective and safe drugs for the treatment of diabetes and obesity, which is rapidly developing in the most advanced areas of pharmacy. A further development of this group and the solution of the identified problems will open up new opportunities for the treatment of diabetes and its complications.